DEVELOPMENT OF NANOEMULSION TO IMPROVE THE OCULAR BIOAVAILABILITY AND PATIENT COMPLIANCE IN POSTOPERATIVE TREATMENT USING INDOMETHACIN - AJMEERA, DIVYA; MANDA, SARANGAPANI; JANAPAREDDI, KRISHNAVENI; KOLLURI, SUSMITHA (International Journal of Applied Pharmaceutics, 2020)
Objective: To develop a new cationic nanoemulsion (NE) for ophthalmic delivery of indomethacin (IND) to improve the permeability and retention time of formulations, thereby improving the drug's ocular bioavailability. Methods: Based on the solubility profile of indomethacin in various solvents, captex 8000 was selected as oil phase, span 20 as a surfactant and tween 20 as co-surfactant to construct pseudo ternary phase diagrams and nanoemulsion region was recognized. Sonication was used as the method of NE preparation. Optimization was done using 32 factorial designs by considering the oil and the ratio of surfactant to co-surfactant (Smix) quantities as independent variables and evaluated for different physicochemical properties. Ex vivo transcorneal permeability was studied using bovine cornea, the In vivo drug pharmacokinetics of optimized NE and marketed formulation were assessed in rabbit aqueous humor and also in plasma. Results: The mean globule size, zeta potential, viscosity, refractive index, pH, surface tension and the osmolarity values for the prepared indomethacin nanoemulsions (IND-NEs) were found between 129.8±1.1 to 191.4±1.6 nm,+13.20±4.6 to+23.45±4.82, 15.3±0.1 to 32.7±0.0 mPas, 1.346±0.007 to 1.386±0.005, 5.5±0.4 to 6.9±0.9, 32.0±2.6 to 52.3±3.4 mN/m and 303-395 mOsm/l respectively and all these values found to be falling under the recommended values for ophthalmic use. From the In vitro release studies, it was found that the IND-NEs exhibited sustained drug release with 67.91±2.01 to 95.90±1.93 % drug release at 24h when compared to the drug solution which showed 99.81±5.21 % drug release within 2h. The Ex vivo drug permeation through the corneal membrane at 4h from the optimized NE and drug solution was found to be 524±1.5 µg/cm2 and 175±2.6 µg/cm2 respectively. Further, the optimized NE was found to be nonirritant with the lowest ocular irritation potential (Iirr) of 1 towards the rabbit's eyes. The area under the drug concentration vs. time curve for 24h (AUC (0–24h)) for optimized NE and the marketed formulation was found to be 1514.99 ng/ml/h and 974.14 ng/ml/h in aqueous humour; 2266.83 ng/ml/h and 778.15 ng/ml/h in plasma respectively. Conclusion: Due to its improved corneal absorption and prolonged drug release along with less systemic absorption, the optimized NE offers an effective postoperative treatment with increased ocular bioavailability and improved patient compliance with a decrease in the number of installations per day and a decrease or disappearance of systemic side effects of IND.